2016
DOI: 10.1021/acs.organomet.5b00968
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydride Transfer Reactions in (Formazanate)Boron Dihydride Complexes

Abstract: The solution-phase thermolysis of (formazanate)boron dihydrides (LBH 2 ; 2) results in the formation of aminoborane compounds (4) via a series of boron-to-ligand intramolecular hydride transfer reactions. Monitoring the reactions by NMR spectroscopy allowed identification of several intermediates, and a reaction mechanism is proposed. In the case of a ligand with an N-Mes substituent it was possible to characterize an intermediate (7b-i) during this transformation that shows an unexpected cyclohexadiene moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…[29][30] Boron difluoride (BF 2 ) complexes of formazanate ligands have been extensively studied by the Gilroy 31 and Otten 32 groups. These compounds have been used as fluorescent cell-imaging agents, 33 acted as precursors to unusual boron-based heterocycles, [34][35] and employed as electrochemiluminescence (ECL) emitters. 36 By contrast, the coordination chemistry of formazanate ligands and heavier group-13 elements (i.e., Al, Ga, In) has been investigated to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30] Boron difluoride (BF 2 ) complexes of formazanate ligands have been extensively studied by the Gilroy 31 and Otten 32 groups. These compounds have been used as fluorescent cell-imaging agents, 33 acted as precursors to unusual boron-based heterocycles, [34][35] and employed as electrochemiluminescence (ECL) emitters. 36 By contrast, the coordination chemistry of formazanate ligands and heavier group-13 elements (i.e., Al, Ga, In) has been investigated to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…Boron substituents other than F. The production of boron dihydride (BH 2 ) complexes of chelating N-donor ligands offers unique opportunities for further reactivity involving the boron-bound hydrides and a representative reaction involving BH 2 formazanates is shown in Scheme 27. 89 The formazan was converted to its corresponding BH 2 complex 70 by treatment with BH 3 ÁSMe 2 in toluene at room temperature. Heating pure samples of 70 in C 6 D 6 resulted in consecutive thermallyinduced hydride transfer reactions to yield compounds 71-i/ii and 72-i/ii.…”
Section: Group 12 (Zn)mentioning
confidence: 99%
“…Step 4 generates a formally low-valent boron center via transfer of the remaining borohydride to the internal nitrogen atom in 75, which allows DFT calculations (B3LYP/6-31G(d)) indicated that the isomerization step was energetically uphill (5.0 kcal mol À1 for 70 -73) and that all other steps are energetically downhill. 89 These studies provided significant insight into the use of formazanate ligands as redox-active ligands as each hydride transfer corresponds to the transfer of two electrons and a proton and served as a starting point for further reactivity studies. As noted earlier (Scheme 24), a significant hurdle in the development of the two-electron reactivity of complexes of redox-active formazanate ligands is the realization of methods for the production of their dianion form.…”
Section: Group 12 (Zn)mentioning
confidence: 99%
See 2 more Smart Citations